2022
DOI: 10.1093/sw/swac050
|View full text |Cite
|
Sign up to set email alerts
|

On the Frontlines: The Impact of the COVID-19 Pandemic on Social Workers’ Well-Being

Abstract: The crisis created by the spread of COVID-19 brought increasing needs and referrals to social welfare services in many countries. However, at the same time, social services suffered from staff cutbacks and service closures, resulting in significant workload increases to address the hardships associated with the pandemic. This article investigates the impact of the COVID-19 pandemic on Israeli social workers’ well-being, using a mixed-methods design with a sample of 2,542 licensed social workers. Findings show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Despite the increased caseloads, child welfare services operated under frequently modified social-distancing restrictions, which included repeated mandated lockdowns, self-quarantines (Tener et al, 2020 ; U.S. Department of Health and Human Services, 2022 ), staff shortages, and service cutbacks (e.g., Ashcroft et al, 2022 ; Katz et al, 2020 ; Marmor et al, 2021 ). Recent studies have documented the adverse effect of the pandemic on the social work workforce, and revealed that frontline social workers had experienced elevated stress levels (Banks et al, 2020 ; Schwartz-Tayri, 2022 ) because of both their own personal hardships and those of their clients (Holmes et al, 2021 ). While knowledge about the repercussions of the pandemic on the well-being of social workers working with children and families is emerging, empirical research on the job performance of social workers is still lacking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the increased caseloads, child welfare services operated under frequently modified social-distancing restrictions, which included repeated mandated lockdowns, self-quarantines (Tener et al, 2020 ; U.S. Department of Health and Human Services, 2022 ), staff shortages, and service cutbacks (e.g., Ashcroft et al, 2022 ; Katz et al, 2020 ; Marmor et al, 2021 ). Recent studies have documented the adverse effect of the pandemic on the social work workforce, and revealed that frontline social workers had experienced elevated stress levels (Banks et al, 2020 ; Schwartz-Tayri, 2022 ) because of both their own personal hardships and those of their clients (Holmes et al, 2021 ). While knowledge about the repercussions of the pandemic on the well-being of social workers working with children and families is emerging, empirical research on the job performance of social workers is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Still, C.W. social workers worked mainly remotely, via phone calls and video chats, except for family emergencies (Schwartz-Tayri, 2022 ). Most child residential care facilities were closed, forcing children to return to unsafe environments and abusive family members, thereby escalating the children’s exposure to multiple risks (for review, see Sect.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the first studies have been presented that used machine learning for text analysis in social work. As a paper at the ESWRA conference demonstrated, sentiment analysis based on machine learning was used to analyse the expressions of emotion in social workers' written free-text responses to open-ended questions (Schwartz-Tayri, 2022). This computational procedure blurs the boundaries of quantitative and qualitative analysis as do other emerging methods of computational social science, such as topic modelling, network analysis (Franken, 2023) or computational grounded theory (Nelson, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…schools resulted in a learning deficit (14). Closure of services and transition to remote work deteriorated health in certain communities (15)(16)(17)(18)(19).…”
mentioning
confidence: 99%